Signatures of Altered Gene Expression in Dorsal Root Ganglia of a Fabry Disease Mouse Model - Kummer, Kai K.; Kalpachidou, Theodora; Kress, Michaela; Langeslag, Michiel (Frontiers in Molecular Neuroscience, 2018)
Fabry disease is an X-linked lysosomal storage disorder with involvement of the nervous system. Accumulation of glycosphingolipids within peripheral nerves and/or dorsal root ganglia results in pain due to small-fiber neuropathy, which affects the majority of patients already in early childhood. The α-galactosidase A deficient mouse proved to be an adequate model for Fabry disease, as it shares many symptoms including altered temperature sensitivity and pain perception. To characterize the signatures of gene expression that might underlie Fabry disease-associated sensory deficits and pain, we performed one-color based hybridization microarray expression profiling of DRG explants from adult α-galactosidase A deficient mice and age matched wildtype controls. Protein-protein interaction and pathway analyses were performed for differentially regulated mRNAs. We found 812 differentially expressed genes between adult α-galactosidase A deficient mice and age-matched wildtype controls, 506 of them being upregulated and 306 being downregulated. Among the enriched pathways and processes, the disease-specific pathways “lysosome” and “ceramide metabolic process” were identified, enhancing reliability of the current analysis. Novel pathways that we identified include “G-protein coupled receptor signalling” and “retrograde transport” for the upregulated genes. From the analysis of downregulated genes, immune-related pathways, autoimmune and infection pathways emerged. The current analysis is the first to present a differential gene expression profile of DRGs from α-galactosidase A deficient mice, thereby providing knowledge on possible mechanisms underlying neuropathic pain related symptoms in Fabry patients. Therefore, the presented data provide new insights into the development of the pain phenotype and might lead to new treatment strategies.